Meningkatkan Kemampuan Mengenal Bentuk Geometri Melalui Ape Maze Geometri pada Anak Usia Dini - Syamsul Muarif; Siti Khoirumaroh; Asri Widiatsih (STKIP PGRI SITUBONDO, 2025)
Problems in the field based on the known that the ability of children who know or identify geometric shapes is still lacking because only 13 children out of 18 children there are still those who do not know about geometric shapes, can not distinguish geometric shapes. The purpose of this study was to determine whether through APE Maze Geometry can improve the ability to recognize geometric shapes. This research uses Classroom Action Research or PTK. the subject of this research is the students of Kindergarten A Pertiwi 37 Kaligondo Banyuwangi which amounted to 18 children. The data collection procedures used in this study are observation techniques, and documentation.The results of the study obtained a percentage increase during the pre-cycle phase and after the implementation of class action showed an increase. Based on the observation results, it is known that there were 2 children (11.1%) who had BSH and BSB criteria at the pre-cycle stage, but after the first cycle of action was carried out this number increased to 10 children (55.5%), and even higher to 17 children (94.4%) in cycle II which shows that some children have reached the BSH criteria and are doing very well. It can be concluded that APE Maze Geometry is an APE that can improve the ability to recognize geometric shapes for group A children. This research shows that children's understanding of geometry concepts can be improved through the use of play-based learning strategies such as APE Maze Geometry.